ANALYSIS OF INTERLINGUAL ERRORS IN ENGLISH IN ELEMENTARY SCHOOL STUDENTS - Kadek Adyatna Wedananta (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2020)
ABSTRAK: This study analyzes such interlanguage errors in five private English students with low school grades. That is why some of these students' interlingual errors are easy to spot. The use of English must take place during a private course in English. This can happen from teacher to student or from student to teacher, or it can occur when certain written activities are completed by students. This study found evidence that English was still used at the Interlanguage (IL) level because although they used English, some students still had interlingual errors, such as the use of To Be, prepositions and adjectives / nouns, etc. This study also finds a technique by which teachers solve the interlingual error problem by using Drill method, which allows them to repeat the use of To Be, adjectives, etc. Keywords: Second Language Acquisition, Interlingual Errors, Drill Method